RECURRENT AND/ OR PERSISTENT WHEEZING IN INFANTS UNDER 1 YEAR OF AGE (Vietnam Journal of Community Medicine, 2026)
Wheezing is one of the most common respiratory symptoms in infants. The causes of wheezing are very diverse and the treatment is also different depending on the causes.Objective: To determine some causes of recurrent and/or persistent wheezing in children under 1 year old.Methods: A cross-sectional descriptive study was conducted on 117 children under 1 year old with recurrent and/or persistent wheezing at the Respiratory Center, National Children's Hospital, from July 2024 to June 2025.Results: Airway abnormalities and persistent wheezing after viral infection were the two most common causes of recurrent and/or persistent wheezing in children under 1 year old. Among these, the group of wheezing due to airway abnormalities, particularly congenital structural airway abnormalities, was prominent. The group of children with wheezing before 6 months of age often experienced persistent wheezing, and most were diagnosed with airway abnormalities. The group with wheezing after 6 months of age included both recurrent and persistent wheezing.Conclusion: Airway abnormalities and persistent wheezing after viral infection are the most common causes of recurrent and/or persistent wheezing in children under 1 year old. The age of wheezing onset is valuable in guiding the diagnosis of the underlying cause.
Keywords: Wheezing, recurrent, persistent, children under 1 year old.